PENGARUH PENERAPAN SYNECTICS LESSON DALAM PEMBELAJARAN IPA FISIKA UNTUK MENINGKATKAN KOMPETENSI SISWA KELAS VIII DI SMPN 1 SOLOK - Rizki Khairani (Universitas Negeri Padang, 2013)
The low of student competencies achievement in Physics-Nature Science learning due to the lack of effective learning model that is applied in the learning process, particularly in enhancing student’s creativity. Synectics Lesson is one model of learning that are considered effective to enhance student’s creativity, because there is a methapor in which the activity. Therefore, conducted research to investigate the affect of applying Synectics Lesson in learning of Physics science to increase students competence. Quasi Experiment Research with Randomized Countrol Group Only Design consist of two independent predictor variables. Populations of the research is all of student VIII grade in SMPN 1 Solok City enrolled in the academic year 2012/2013 unless the class is seeded. Sampling was done by using Cluster Random Sampling. Instrument such as the end of the test item for general cognitive, creative thinking scoring rubric, observation sheet creative attitude, scoring rubric creative skills, obeservation sheet implementation of models, student worksheet and questionnaires. Data belonging to the primary data which are analyzed using two test average similarity, multiple regression testing, product-moment correlation test at 0,05 significance level. The results showed that Synectics Lesson have a significant impact on increasing student competence quantitatively with high criteria at 0,05significance level. Keywords : Synectic Lesson, Metaphor Activity , and Creativity